01 PROSPEK PENGEMBANGAN USAHATANI KACANG TANAH (Studi Kasus Desa Limampoccoe Kecamatan Cenrana Kabupaten Maros) - Jurnal Agribis; Hasmawati Hasmawati; Arifin Arifin; Muhammad Risal (Universitas Muslim Maros, 2021)
Peanut agribusiness in this area has prospects to be developed considering that the available land resources are quite extensive, suitable climatic conditions, sufficient peanut cultivation technology is available, human resources are quite skilled in farming and the market is still wide open for peanut commodities. This research was carried out in Cenrana District, Maros Regency, this location was chosen because most of the villagers produce peanuts. There are two data used: primary data, namely data obtained from observations through direct interviews and also through the help of questionnaire lists, and secondary data, namely data obtained from agencies / institutions that are related or related to this research. The purpose of this study was to determine the prospects for developing peanut farming and to know the results of the production of farmers in the District of Cenrana. Data was collected from the survey results using a questionnaire and supplemented with observations / field observations. The data that has been collected is then tabulated to get the real data used for analysis. This study uses the SWOT Analysis method to determine the prospects for developing Peanut Farming in Cenrana District, Maros Regency, the results of the production of Peanut farmers. The results of this research can be seen the prospect of developing peanut farming is in quadrant I (one). This quadrant illustrates a very favorable situation for developing the farming business.